Impacts of Stress and Risk Perception on Mental Health of College Students During the COVID-19 Pandemic: The Mediating Role of Coping Efficacy - Xu, Fuming; Huang, Long (Frontiers in Psychiatry, 2022)
Object: In this study, we aimed at exploring the influences of Chinese college students' epidemic stress, risk perception and coping efficacy on their mental health during the COVID-19 epidemic. Methods: A nationally representative sample of 3,381 Chinese college students took part in an online survey during the COVID-19 epidemic. Correlation coefficients, structural equation modeling, and other statistics were used for data analysis. Results: (1) Chinese college students' epidemic stress and epidemic risk were at the medium level (3.51±0.83, 3.45±0.94 ), while the perceived infected risk was at a lower level (2.10±0.67). College students’ mental health level during COVID-19 epidemic is at a good level (3.80±0.73). (2) College students’ mental health was significantly negative associated with epidemic stress, perceived epidemic risk, perceived infected risk. College students’ mental health was significantly positive associated with coping efficacy; College students’ coping efficacy was significantly negative associated with epidemic stress, perceived epidemic risk, perceived infected risk. Conclusion: Coping efficacy played a partial mediating role between epidemic stress and mental health; Coping efficacy played a partial mediating role between perceived infected risk and mental health; Coping efficacy played a complete mediating role between perceived epidemic risk and mental health. Our findings showed the importance of fostering college students’ coping efficacy to their mental health during the COVID-19 epidemic.